1992
DOI: 10.1203/00006450-199211000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Treatment of Pediatric Cholesteryl Ester Storage Disease with Lovastatin

Abstract: ABSTRACT. The aim of this study was to prospectively assess the safety and efficacy of lovastatin in the treatment of cholesteryl ester storage disease in siblings who were ages 11.6 and 5 y at the beginning of treatment. Mean total and LDL cholesterol in the male proband, 7.40 and 5.68 mmol/L, respectively, on diet alone, fell 30% to 5.2 ( p 5 0.001) and 31% to 3.9 mmol/L ( p 5 0.001) on lovastatin 40 mg/d over 3.3 y, with simultaneous resolution of hepatosplenomegaly. In his sister, on lovastatin 20 mg/d for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Lovastatin and simvastatin have both been utilized in the clinic with varying rates of success. In some cases, statin therapy reduced hepatosplenomegaly and TG/CE levels in serum and in the liver [74, 95-97] while in other cases the reduction in TG/CE levels was not significant [98, 99]. The efficacy of statins is augmented when used in combination with other cholesterol lowering drugs, such as ezetimibe [100] and cholestyramine [101].…”
Section: Introductionmentioning
confidence: 99%
“…Lovastatin and simvastatin have both been utilized in the clinic with varying rates of success. In some cases, statin therapy reduced hepatosplenomegaly and TG/CE levels in serum and in the liver [74, 95-97] while in other cases the reduction in TG/CE levels was not significant [98, 99]. The efficacy of statins is augmented when used in combination with other cholesterol lowering drugs, such as ezetimibe [100] and cholestyramine [101].…”
Section: Introductionmentioning
confidence: 99%
“…The suppression of cholesterol synthesis and apolipoprotein B production by 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors (HMG CoA reductase inhibitors) can be considered as a useful therapeutic principle. Several authors have found beneficial results with lovastatin [16][17][18][19] and simvastatin [20], both alone and in association with cholestyramine [21], and ezetimibe [22] in reducing serum concentrations of total cholesterol, low-density lipoprotein cholesterol, and triglycerides in young patients with CESD. However, the benefit of this therapy has been questioned by other authors [23].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of two studies in patients with NS only adds another 16 children. Children with unusual lipid abnormalities, such as Alagille's syndrome, cholesterol ester storage disease (CESD), and sitosterolemia, have also been prescribed statins, but the results are generally limited to individual patient responses that may be biased to the reporting of patients who responded rather than those who did not [27][28][29][30]. A similarly small number have been treated with very high doses of statins, with mixed results on neoplasms.…”
Section: Present Experience With Statinsmentioning
confidence: 99%